UMPSA and Northern Illinois University (NIU) strengthen their cooperation network - Mimi Rabita, Abd Wahit (UMPSA, 2024)
KUALA LUMPUR, 12 January 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is set to enhance its collaboration network with Northern Illinois University (NIU), United States of America, to offer an Engineering Technology Programme aimed at producing more Practical Engineers or Technologist graduates in the country.